Current Status of Solar-Thermal and Solar-Photovoltaic Technology Development at the International Level - Vanegas-Chamorro, Marley; Cely-Bautista, María Mercedes; Villicaña-Ortiz , Eunice; Mendoza-Cáceres, Daniel; Visbal-Vanegas, Valeria (International Journal of Energy Economics and Policy, 2022)
This article shows the trend in the development of solar thermal and solar photovoltaic technologies and their impact on developing more efficient and sustainable systems based on a bibliometric and scientometric study from 2000-2022. By conducting a bibliometric analysis, the incidence of publications related to the topic was determined, concerning the countries with the highest production, institutions, most representative authors, and keyword analysis, among others; in addition, the study of patents related to the topic was analyzed. The databases Scopus, Journal citation report, Espacenet software, and different computer tools were used for the analysis. The results showed that the countries with the most significant impact and production of technologies are the United States, India, China, Spain, and Brazil, which account for more than 50% of the total. The United States is the country that produces the most patents